Mother of Gods, Mother of Harlots: The Image of the Mother Goddess Behind the Depiction of the "Whore of Babylon" in Revelation 17 - Schedtler, Justin Jeffcoat (Novum Testamentum, 2017)
One of the primary interpretive challenges in the study of Revelation 17 has been to ascertain the identity of an historical personage or entity evoked by the description “Whore of Babylon.” This paper explores a previously neglected figure, Cybele the “Great Mother” Goddess. Through an examination of the artistic, archaeological, and literary evidence relating to the Mother Goddess during the time of her greatest flourishing in the Roman periods, several elements of the description of the Harlot in Rev 17 can be understood to evoke Cybele. Insofar as the Mother Goddess was closely associated with Roman socio-political-religious systems, this scene constitutes an attack on the Roman Imperial apparatus.